2021
DOI: 10.1007/s13555-021-00660-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Risankizumab on PASI90 and DLQI0/1 Duration in Moderate-to-Severe Psoriasis: A Post Hoc Analysis of Four Phase 3 Clinical Trials

Abstract: Introduction: Novel therapies have allowed psoriasis patients to achieve high levels of skin clearance and meaningful improvements in health-related quality of life measures; however, duration of these outcomes has not been evaluated. This study aimed to estimate the duration of Psoriasis Area and Severity Index (PASI) 90 and Dermatology Life Quality Index (DLQI) 0/1 among patients with moderate-to-severe psoriasis receiving risankizumab and other treatments. Methods: Pooled data from four phase 3 randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It has been approved by European Medicines Agency in April 2019 for the management of moderate‐to‐severe psoriasis and in 2021 for the treatment of psoriatic arthritis. Its efficacy and safety were showed by several clinical trials 16,17 . Particularly, risankizumab has been showed to be more effective than adalimumab, secukinumab and ustekinumab 18–20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been approved by European Medicines Agency in April 2019 for the management of moderate‐to‐severe psoriasis and in 2021 for the treatment of psoriatic arthritis. Its efficacy and safety were showed by several clinical trials 16,17 . Particularly, risankizumab has been showed to be more effective than adalimumab, secukinumab and ustekinumab 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…Its efficacy and safety were showed by several clinical trials. 16,17 Particularly, risankizumab has been showed to be more effective than adalimumab, secukinumab and ustekinumab. [18][19][20] Promising results have been showed in real-life settings as well.…”
Section: Introductionmentioning
confidence: 99%
“…Given the small number of clinical trials and systematic reviews, case series have been included, despite the fact that the evaluation of efficacy and effectiveness in them is very limited. 19–30 The studies that have been evaluated are: 8 clinical trials with high evidence, 19 , 20 , 23–26 , 28 , 29 3 case series, one prospective, 21 and 2 retrospective, 22 , 27 of which the evidence is of low quality, and a cohort study of medium evidence quality. 30 …”
Section: Resultsmentioning
confidence: 99%
“… Low Lebwohl. et al 23 Design: Clinical Trial Aim : This study aimed to estimate the duration of PASI 90 and DLQI 0/1 among patients with moderate to severe psoriasis receiving RZB and other treatments. Endpoints : PASI 90, DLQI 0/1 Pivotal trial patients : *UltIMMa-1, UltIMMa-2, IMMvent, and IMMhance Overall population: =2101 RZB only=895 RZB and RZB/PBO=406 ADA and ADA/RZB=303 PBO/RZB=300 UltIMMa-1, UltIMMa-2, IMMvent, and IMMhance Patients treated with only RZB throughout the study period experienced the longest DLQI 0/1 duration from baseline to week 52 [213.7 days (59% over 1 year)], followed by patients who received ADA and ADA/RZB [159.1 days (44% over 1 year)], and only UST [144.3 days (40% over 1 year)].…”
Section: Resultsmentioning
confidence: 99%
“…Its safety and efficacy profiles have been evaluated by several trials and real world evidence studies, which confirmed risankizumab promising results in the management of moderate to severe psoriasis. [106][107][108][109][110] Tildrakizumab represents the latest IL-23 inhibitor available in clinical practice in Italy. It is a fully humanized IgG1/k antibody selectively binding to the p19 subunit of the IL-23.…”
Section: Anti-il23mentioning
confidence: 99%